Social Psychiatry and the demand for Mental Health Services: Some caution is valid? - Pereira, Izadora de Sousa; Macêdo, Amanda Plácido da Silva; Sá, Ivna Celli Assunção de; Moreira, Larissa Melo; Rolim Neto, Modesto Leite (Amadeus International Multidisciplinary Journal, 2019)
Mental health in the interface with social psychiatryis a constantly evolving field. Psychiatry faces major challenges. The therapeutic relationship remains paramount. Methods: A Short Communication that focus the informational spaces of professional interests, many new ideas and concepts what are issued under the banner of "social psychiatry.". Include: discovery or development of new information’s, novelty in modeling scientific and channels of information. Results: The evidences emphasize that Mental illness and interventions in psychiatry should be considered in the of social context where patients live and factors they face on a daily basis. There’s a need for greater numbers of psychiatrists. Limitations: As Short Communications are expected to have higher than average impact on the field rather than report on incremental research, they will receive prioritized and rapid publication. Conclusion: Social values and concepts have played a central role in the history of mental health care, allowing more focus on possible environmental causes or factors. Keywords: Social Psychiatryis; Mental Health; Therapeutic Relationship.